KANDASNYA KRIMINALISASI PERKARA PERDATA MURNI - Sholahuddin Harahap (Komisi Yudisial RI, 2011)
ABSTRACTTGHC, ETRL and PTGI (the three legal companies established under the laws of British Virgin Island) have agreed to hold an agreement set forth in notarial deeds. In practice, there were conflicts of management, ownership of shares, and breach of contract. The parties sued each other. The judiciary, in this case the High Court of British Virgin Island, finally dropped its decision. However, after receiving files from the criminal investigators, public prosecutors still filed the case to the Central Jakarta District Court. The author of this article analyzes the decision of the Central Jakarta District Court over the case. He also distinguished the court rulings between the terms of